Marx 1843. Una critica mancata - Ventura, Andrea (Il sogno della farfalla, 2007)
This article reconstructs the research carried out by Marx, with particular focus on his main writings in the period 1841-44. The author aims to show that having reached the concept of economic materialism, discovering the revolutionary role of the proletariat and defining communism as the “resolved enigma of history” are all a consequence of the failure of Marx’s research into the problem of religious alienation. Some of Marx’s intuitions are then discussed and compared to the theses of Locke on knowledge, tolerance and the centrality of property rights. The aim is to show that one cannot propose to overcome religious alienation and the centrality of property rights without a critique of a system of thought and a theory of knowledge based on reason, a critique which Marx failed to carry out.